Loss of control eating and weight outcomes after bariatric surgery: a study with a Portuguese sample - Conceição, Eva Martins (2014)
The present study aim is to investigate the frequency of loss of control eating (LOC) episodes in three groups with different assessment times: one before, one at short and one at long-term after bariatric surgery; as well as to explore the association of postoperative problematic eating behaviors and weight outcomes and psychological characteristics. This cross-sectional study compared a group of preoperative bariatric surgery patients (n = 176) and two postoperative groups, one at short-term with < 2 years follow-up (n = 110), and one at long-term > 2 years follow-up (n = 53). Assessments included the EDE diagnostic interview and a set of self-report measures assessing eating disordered symptomatology, depression, and body image. We found the presence of LOC in 26.7 and 16.9 % of the pre-operative and long-term patients, respectively, and in about 11.8 % of the short-term patients. One patient (0.9 %) reported objective binge eating episodes at short-time, but subjective binge eating episodes were present in about 10 % of the patients in all groups. LOC eating was related with the highest BMIs, the least weight loss, most weight regain, and most psychological impairment in the long-term assessments, but not at short-term. Despite the lower frequencies of disordered eating behavior in the short-term group, patients reporting LOC seem to represent a subgroup of individuals with poorest outcomes after surgery and most psychological distress.